The Impact of Covid-19 on Urban Planning of Port Harcourt City, Nigeria - Odigwe, Moses; Mchi, Akaawase Alexander (Nepal Journal of Multidisciplinary Research, 2024)
Background: Coronavirus disease is a communicable and contagious respiratory disease that has not only affected human social lives, interactions and relationships but equally changed other significant patterns of people’s normal lives, and there is need for a robust urban planning to meet the emerging changes. This study sought to investigate how the COVID-19 pandemic has affected the inhabitants of Port Harcourt City and its implications on urban planning in Port Harcourt City, Nigeria. This study examined how the COVID-19 pandemic affected human interactions and business activities, and its implication on urban planning in Port Harcourt city. Methods: The study adopted descriptive survey design with questionnaire used for data collection. Port Harcourt inhabitants aged 18 years and above were studied using four major clusters in Port Harcourt city. Purposive sampling technique was used to select participants from five most affected COVID-19 business areas in each cluster in the year 2020. A total of 400 participants assessed on people’s economic activities and welfare attributes using Likert-scale. Data were analysed using simple percentages, mean and standard deviation. Results: Major findings revealed that COVID-19 negatively affected the lives of people, closure of markets and other economic centres, lack of face-to-face communication and interaction, change in people’s social welfare and lifestyle, to halt in education and academic activities, restriction in movement and transportation, and household welfare challenges. It is suggested that policymakers should intensify efforts to ensure coronavirus is eradicated by providing COVID-19 drugs to all Nigerians. Conclusion: The study underscores the urgent need for comprehensive measures to mitigate the multifaceted impacts of COVID-19 in Nigeria, emphasizing equitable access to essential medications as a crucial strategy for combating the pandemic's adverse effects on society. Novelty: This research offers novel insights into the broad-ranging impacts of COVID-19 on various aspects of life in Nigeria, highlighting the imperative of equitable access to medications as a pivotal solution.